From Knowledge to Income: Islamic Values-Based Women’s Economic Empowerment Model Through Traditional Knowledge in East Java - Fuad, Zainul; Rohmah, Nafilatur (PALASTREN: Jurnal Studi Gender, 2025)
Rural women in Indonesia face a paradox: they produce 50% of the food but earn only 10% of the agricultural income. This study explores how traditional food processing knowledge can serve as economic capital for women within an Islamic values framework. Through Participatory Action Research with 25 women sapodilla processors in Brondong Subdistrict, Lamongan Regency, East Java (March 2023-February 2024), we documented real economic transformation. Applying the Harvard Gender Analysis Framework, results show a 212% increase in monthly income (from IDR 285,000 to IDR 890,000, p<0.001), 76% increase in decision-making autonomy, and a reduction in middleman dependency 85% to 33%. Findings confirm that recognition and monetization of women’s traditional knowledge, aligned with Islamic principles of kasb (work earnings), offer sustainable pathways for economic empowerment in rural Indonesia.